The market and policy development of EV industry on a global level and in Uzbekistan - Review (Texas Journal of Multidisciplinary Studies, 2022)
This paper reviews the historical and recent growth of the global EV industry and examines the importance of green vehicles in sustainable development. Notably, the study describes the situation in the leading EV markets in terms of the market situation, legislative aspects, and infrastructural development. The paper finally examines the EV market in Uzbekistan and the local government's official position on adopting electric vehicles. The study found that the EV industry in Uzbekistan is at the infant stage, and a great deal remains to be done in legal and infrastructural improvements to reach the market level of other leading countries. The paper also showed the implication of EVs' adoption in parallel with other favorable reforms in Uzbekistan. Further research into the EV industry of Uzbekistan is recommended to accurately assess the needed level of monetary incentives through the analysis of the current and future market capacity and administrative budget